Design and Production of Trophies for Selected Sports and Games in KNUST (Journal of Science and Technology, 2016)
Design and production of trophies for games and sports particularly in a form of metal art has been in existence for so many years. Presently they are practiced with much improvement and modern technology as compared to the ancient times where leaves, horns and other objects were used as trophies to award warriors and those who excelled in other sporting disciplines. Trophies are said to be prizes or cups which are given to an individual, a group of people or a nation for performing excellently in any sporting activity such as tennis, football, volley ball, basket ball and horse racing etc. Today, trophies serve so many purposes, such as, a souvenir of remem-brance; as a stool for one to look at and strive for excellence in life as well as financial gains. KNUST does not have its own trophies for the Sports and Games they engage in. This publica-tion seeks to display the design and subsequent production of four trophies for Kwame Nkrumah University of Science and Technology (KNUST) to enhance the prestige of its awards and solve some related problems. The technique for production is the lost wax. Metal scraps such as brass and copper were the main materials used for the production. Especially the lost wax technique of production was very efficient and effective in the production of the trophies. Experimental and Descriptive Research methods based on the quantitative and qualitative research approaches were employed. It is recommended that Metalsmiths and other Metal Artists as well as students experiment with other materials and techniques in the production of trophies to bring variety in the field of trophy production.